Increased Horizontal Transmission of Recombinant Marek’s Disease Virus Due to Reticuloendotheliosis Virus Long Terminal Repeat Is the Major Competitive Advantage of the Virus Being a Prevalent Strain - Su, Shuai; Cui, Ning; Li, Yanpeng; Yu, Meng xin; Zhang, Ting; Cheng, Ziqiang; Chai, Jiaqian; Cui, Zhizhong; Chen, Ruiai (Frontiers in Microbiology, 2019)
GX0101 is the first field Marek’s disease virus (MDV) recombinant with an REV LTR insert isolated in China. We speculated that there was a selective advantage of GX0101 becoming the more prevalent field strain from a very low percentage of recombinant virus. In the study, dual fluorescence quantitative real-time PCR (DF-qPCR) that detects GX0101 and GX0101∆LTR simultaneously was established based on the genomic difference of GX0101 and its LTR deletion strain GX0101∆LTR. MDV natural transmission was simulated in SPF chicks and continuous tracking of GX0101 and GX0101ΔLTR in chicks was carried out. The results showed that GX0101 possessed high horizontal transmission capacity, which could infect SPF chicks by contact in a short time and became the predominant strain following contact infections in chicken flocks. GX0101 still had a more significant advantage of horizontal transmission than GX0101∆LTR after continuous passage even the initially infectious dose was significantly lower. There were 72 differentially expressed MDV genes between GX0101 and GX0101∆LTR, with the genes and gene products mainly involved in virus replication, tegument protein, glycoprotein, Nucleocapsid protein, immune evasion, tumor development and/or pathogenesis, hypothetical protein. Sixteen genes related to virus replication and transmission were significantly up-regulated. This is the first study to illuminate that increased horizontal transmission of recombinant MDV due to REV LTR was the competitive advantage of the virus being a prevalent strain and define the differential transcription profile of viral genes between GX0101 and GX0101ΔLTR. This will be helpful for in-depth study on the molecular mechanism of increased horizontal transmission of MDV by REV LTR.